On Measuring the Variation of High-energy Cutoff in Active Galactic Nuclei - Zhang, Ji-Xian; Wang, Jun-Xian; Zhu, Fei-Fan (The Astrophysical journal, 2018)
The variation in the high-energy cutoff, Ec, in active galactic nuclei (AGNs) uniquely probes the corona physics. In this work, we show that the ratio of two NuSTAR spectra (analogous to the difference-imaging technique widely used in astronomy) is uniquely useful in studying Ec variations. The spectra ratio could directly illustrate potential Ec variation between two spectra. By comparing with the ratio of two spectral-fitting models, it also examines the reliability of the spectral fitting measured Ec variation. Assisted with this technique, we revisit the five AGNs in the literature (MCG-5-23-16, 3C 382, NGC 4593, NGC 5548, and Mrk 335), for which Ec (kTe) variations have been claimed with NuSTAR observations. We show that the claimed Ec variations appear inconsistent with the spectra ratios in three of them, thus they need to be revised, demonstrating the striking usefulness of spectra ratio. We present thereby improved spectral-fitting results and Ec variations. We also report a new source with Ec variations based on NuSTAR observations (radio galaxy 4C+74.26). We find the corona tends to be hotter when it brightens (hotter-when-brighter) in 3C 382, NGC 5548, Mrk 335, and 4C+74.27, but MCG-5-23-16 and NGC 4593 show no evidence of significant Ec variations. Meanwhile, all six sources in this small sample appear softer when brighter. Changes in corona geometry are required to explain the observed hotter-when-brighter trends.